STUDI LITERATUR: KOMPETENSI AUDITOR DAN KEAHLIAN SISTEM INFORMASI AUDITOR TERHADAP PEMBUKTIAN FRAUD - rahmawati, Debby Yusriliana; Ratnawati, Tri (Pro-fit, 2024)
ABSTRACT One part of these efforts is to increase supervision and guidance of the apparatus to stop corrupt behavior in the work environment, and to fully support efforts to prosecute corruption carried out by the Indonesian National Police, the Attorney General's Office of the Republic of Indonesia, and the Corruption Eradication Commission (KPK) by accelerating the dissemination of information about corruption cases and accelerating examination permits for corruption cases. Apart from having to understand auditing and accounting, investigative auditors must also understand the law in relation to cases of irregularities or fraud that can harm State finances (Karyono, 2013: 132). Investigative auditors must have the ability to prove the existence of fraud that may occur and has been detected by various parties before conducting an investigative audit. One of these responsibilities is that investigative audits must be carried out by officers who have the necessary expertise. Auditors must have the ability to prove possible fraud that has been pointed out by various parties beforehand. Auditors have technical expertise, which consists of procedural knowledge and other clerical skills in accounting and auditing. Keywords : Auditor Competency, Auditor Independence, Auditor Information System, Audit Investigation.